2021
DOI: 10.1007/s10639-021-10534-y
|View full text |Cite
|
Sign up to set email alerts
|

Contextualized game-based intervention for digital literacy for the Pacific Islands

Abstract: In the digital age, advocating and improving digital literacy is a global challenge. There have been scales developed to measure individuals' digital literacy competencies; however, intervention programs have been only a few. This research paper articulates design details, validity, reliability and effectiveness of a new online modulated digital literacy intervention program (DLIP). For the development of DLIP, digital literacy is stipulated in this research as a universal framework that consists of six differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Advocating information literacy through gamification is also suggested for the Fijian students. A recent study done by (Reddy et al , 2021) showed an initial step of using game-based intervention to improve digital literacy in the Fiji Islands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advocating information literacy through gamification is also suggested for the Fijian students. A recent study done by (Reddy et al , 2021) showed an initial step of using game-based intervention to improve digital literacy in the Fiji Islands.…”
Section: Resultsmentioning
confidence: 99%
“…Digital literacy and information literacy are two essential and active components in the South Pacific. Several studies have been conducted on digital literacy in the South Pacific by the current authors (Reddy et al , 2020b, 2021) and studies on information literacy have just revealed the importance of information literacy for South Pacific students (Chief et al , 2014). As indicated in the introduction section of this paper, there is no study conducted on measuring the information literacy competencies of the individuals in the South Pacific.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…However, different authors define digital literacy differently due to the emerging applications and digital technologies. Unlike Gilster (1997), Reddy et al (2021) introduce the digital literacy framework. The digital literacy umbrella encompasses many complex and integrated sub-competencies: media, information, visual, communication, computer, and technology.…”
Section: Digital Literacy or Digital Competence?mentioning
confidence: 99%
“…However, it requires educators to develop the skills and competencies to perform tasks and solve problems. Digital Literacy (DL) summarizes these aforementioned skills, while also providing the foundation of various measuring scales to rely on while evaluating an educator as digitally literate (Reddy et al, 2020;Reddy et al, 2021). Developing DL among educators will contribute towards the achievement of UNESCO´s GEA mission.…”
Section: Introductionmentioning
confidence: 99%